Evaluasi Pengalaman Pengguna untuk Aplikasi PayPal Menggunakan Metode Kuesioner Pengalaman Pengguna (UEQ) - Imam Zada Ainullah; Muhammad Husni Syahbani; Dwi Rosa Indah (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2026)
Digital transformation and financial inclusion have driven the increased use of digital wallets and online transactions, PayPal as one of the largest digital payment services. However, the user responses to the quality of PayPal's systems and services are still diverse. This study aims to evaluate the user experience of the PayPal application version 8 using the User Experience Questionnaire (UEQ) method. The results showed that PayPal scored very well in attractiveness with a score of 1.82, efficiency (1.67), dependability (1.66), stimulation (1.78), and novelty (1.61), and it placed PayPal above 75% of the similar apps. Even though clarity, with a score of 1.72, was rated